SOCIOLOGY AND SOCIAL CRITICISM: CRITICAL REASONING MODELS - A. V. Scherbina (Дискурс, 2016)
This article discusses the impact of the critical tradition in sociology on social criticism. High relevance of the sociological critical reasoning models in modern social criticism is shown. A drift from critical macrodiagnostics of the modern society to interpretation of local critical discourses in sociology is analyzed. The necessity to restore the regulatory focus of sociological criticism is sunstantiated.